Road Transportation Energy Demand and Environmental Emission: A Case of Kathmandu Valley - Bajracharya, Iswor; Bhattarai, Nawraj (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
The current trade embargo imposed by India has created an acute fuel crisis in Nepal which has stranded more than 50% of public vehicles affecting the supply of all the necessities and daily life of people. This study has shown some alternative ways to manage the vehicle fuel demand especially for urban transportation in the Kathmandu valley, Nepal. The modeling tool, Long-range Energy Alternative Planning System (LEAPS) has been used to develop a bottom-up model to estimate the energy demand and environmental emissions in the Kathmandu valley for the period 2016-2030 AD. Besides the Reference scenario, four alternative scenarios (Public Bus Penetration, Improved Fuel Economy, Electric Motorbike and Hybrid Electric Car) have been developed. In the Reference scenario, the cumulative energy demand will reach 142,092 thousand GJ within the analysis period. About 65% of this demand comes from motorbikes and light duty vehicles. If all of the alternative scenarios are implemented together, about 38% of energy demand and 54% of CO2 emission can be avoided compared to the reference scenario within the study period. About 1641 million US$ at the current market price can be avoided within the analysis period if all of these four options are applied together. HYDRO Nepal: Journal of Water Energy and Environment Volume 18, 2016, January Page 30-40